Cultural Meaning of Pahili Mbuala Customary Ritual Speech in Rindi Village, East Sumba Regency: Ethnolinguistic Study (Universitas Negeri Semarang, 2020)
The traditional pahili mbuala ritual utterances used by the performers of the ritual can implicitly represent the culture of the unique Sumba ethnic community. These particularities are full of meanings that can be known through teachings spoken for generations by ritual practitioners.The purpose of this study was to analyze the form of lingual units and the cultural significance of the traditional pahili mbuala ritual speech in Rindi Village, Rindi District, East Sumba Regency.The data in this study are qualitative data using the refer method followed by a competent free engage listening technique (SBLC), record technique, and note-taking technique. Data analysis was carried out through two procedures namely analysis during the process of presenting data and analysis after data collection. The results of the study showed that the form of a lingual unit of traditional pahili mbuala ritual speech in the form of words, phrases, sentences, and discourse can reveal cultural meanings that reflect the thought patterns and views of the Sumba ethnic community on the values ​​and teachings adopted.